2010
DOI: 10.1177/0959683610378882
|View full text |Cite
|
Sign up to set email alerts
|

A thousand years of human impact in the northern Scandinavian mountain range: Long-lasting effects on forest lines and vegetation

Abstract: The vegetation history has been examined by pollen, microscopic and macroscopic charcoal analyses in the vicinity of two alpine Stállo settlement sites and one forested 'Reference area' with no settlement remains in northwestern Sweden in the northern part of the Scandinavian mountain range. The acquired data provide indications of the effects of human activities on local vegetation during the settlement phase, and on ecological processes in both long-and short-term perspectives. The results show that one sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…czerepanovii), based on identification criteria described by Hellberg and Carcaillet (2003), indicating that the settlers used this wood for firewood. Pollen analyses have also shown that mountain birch forests around Stállo settlements in four different areas were cut (Karlsson et al, 2007;, Staland et al, 2011. However, no remains of these buildings exist today, apart from the foundations.…”
Section: Stállo Settlements In the Scandinavian Mountainsmentioning
confidence: 99%
See 3 more Smart Citations
“…czerepanovii), based on identification criteria described by Hellberg and Carcaillet (2003), indicating that the settlers used this wood for firewood. Pollen analyses have also shown that mountain birch forests around Stállo settlements in four different areas were cut (Karlsson et al, 2007;, Staland et al, 2011. However, no remains of these buildings exist today, apart from the foundations.…”
Section: Stállo Settlements In the Scandinavian Mountainsmentioning
confidence: 99%
“…In a multidisciplinary study of such Stállo settlements in northern Sweden, extensive dating of the charcoal found in the hearths indicated that these settlements were mainly used between AD 700 and 1150 (2σ) . The settlements were eventually completely abandoned, probably due to a shortage of firewood, and the lack of trees combined with a colder climate during the Little Ice Age subsequently prevented reforestation (Karlsson et al, 2007;, Staland et al, 2011. Hence, the vegetation changed from mountain birch forest with herbs to open alpine heath dominated by dwarf-shrubs due to human exploitation, nutrient-depleted soils and the harsh climate (Staland et al, 2011).…”
Section: Stállo Settlements In the Scandinavian Mountainsmentioning
confidence: 99%
See 2 more Smart Citations
“…in the more heavily populated areas of Europe (Kaplan et al 2009;Ludemann 2010) and elsewhere (Lev-Yadun et al 2010). Although our data suggest that Sami pre-industrial land uses had very weak effects on the availability of specific resources from a landscape perspective, specific case-studies have detected long-lasting local ecosystem effects, such as vegetation changes due to cutting of firewood (Josefsson et al 2010a;Staland et al 2011;Ö stlund et al 2015) and both above-and below-ground feedback effects of trampling and organic matter transfer (Freschet et al 2014). In addition, case studies have also detected strong cultural imprints in local hotspots (Berg et al 2011;Sjögren and Kirchhefer 2012;Rautio et al 2014).…”
Section: Quantitative Comparisons and Sustainabilitymentioning
confidence: 99%